(untitled) (Journal of Biomedical Investigation, 2008)
The present study was designed to assess the prevalence of malaria and splenomegaly in children under the age of 13 years. A total of 720 children who presented with clinical signs and symptoms of malaria in the study area were recruited. Blood samples were collected in EDTA tubes. Giemsa stained thick and thin smears were microscopically examined to confirm malaria diagnosis. Haemoglobin (Hb) genotype was determined by alkaline cellulose acetate electrophoresis to exclude sickle cell anaemia as possible cause of splenomegaly. Splenic enlargement was determined by palpation. Out of the 720 subjects, 600 (83.3%) were positive for P. falciparum malaria while 114 (15.8%) of these children with malaria. presented with splenomegaly. The result of the Hb genotype showed 576 (80%) of the children were HbAA while 144 (20%) were HbAS. No child with HbSS was seen. The finding showed that malaria is a major cause of splenomegaly in the study area which is an urban setting. The public health implication of the observation is discussed.